Stereotactic Body Therapy for Urologic Cancers—What the Urologist Needs to Know - Jasamine Coles-Black; Adib Rahman; Shankar Siva; Joseph Ischia; Marlon Perera; Damien Bolton; Nathan Lawrentschuk (Life)
Background: stereotactic ablative body radiotherapy (SABR) is a disruptive radiation therapy technique which is increasingly used for the treatment of urologic cancers. The aim of this narrative review is to provide an overview on the current landscape of SABR in urologic cancers and highlight advancements on the horizon. Methods: a narrative review of the contemporary role of SABR in urologic cancers is conducted. Results: in localised prostate cancer, SABR boasts excellent tumour control and biochemical control, with acceptable GU and GI toxicity. Its comparison to laparoscopic radical prostatectomy is currently ongoing. SABR appears to be practical for metastasis-directed therapy in metastatic prostate cancer, with good local control and a low toxicity profile, either alone or in combination with ADT. In localised RCC, SABR offers adequate local control with a modest impact on renal function in patients unfit for surgical management. Its role in metastatic RCC is much more established, where it has been shown to be superior to conventional radiotherapy. Emerging evidence suggests that SABR has a role in delaying systemic therapy whilst maintaining QOL and overall survival. Intriguingly, in metastatic prostate cancer and metastatic RCC, SABR results in a cytoreductive and immunomodulatory ‘abscopal effect’, a focus of current investigations. Conclusions: SABR has emerged as a safe, effective, and feasible treatment for urologic cancers. Urologists should be aware of its increasing use in localised prostate cancer and metastatic RCC, with good oncological outcomes combined with acceptable toxicity. In addition, SABR holds promise for both metastatic prostate cancer and localised RCC treatment in terms of toxicity and oncological outcomes.